EFFECT OF ADDITION OF PANDAN LEAVES (Pandanus amaryllifolius) EXTRACT ON CARRAGEENAN PUDDING - Oktari, Arles; Sari, Ira; Dewita, Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study was aimed to effect of addition of pandan leaves (Pandanus amaryllifolius) extract on carrageenan pudding and produce carrageen pudding which has the distinctive color and odor of Pandan leaves on the manufacture of carrageen pudding and to find out the exact concentration of Pandan extract in the manufacture of carrageen pudding. Based on the research, the effect of addition of pandanleavesextract on carrageen pudding gives the color and the peculiar odor of pandan leaves, very significant effect on organoleptic value, water value, ash value, and carbohydrate value. The treatments were treated with 4 treatment levels: P0 (without pandan extract), P1 (30 ml of pandan extract), P2 (35 ml of pandan extract), P3 (40 ml of pandan extract). The results of selected carrageen pudding was the addition 40 ml of pandan extract with value of appearance (very greenish) 8.41, taste (sweet) 7.24, aroma (very fragrant of pandan aroma) 7.88, texture (solid) 7. 53, and chemical values of water content 19.27%, ash content 3.31%, and carbohydrate content 33.99%. Keywords: Pandanus amaryllifolius, pudding, carrageen